(untitled) (Transactions on Additive Manufacturing Meets Medicine, 2019)
Playing and raving are important for child development. Injuries, diseases or congenital deformities can limit them in doing so. Orthoses that support these children, are usually custom made which requires manual labor. In research, 3D-printig of those devices is often proposed. To have a fully digital process chain, additional techniques are required, which are fundamental for the orthosis fit and efficacy. Within this contribution we describe all necessary steps from recording patient’s individual anthropometric data to automated design of structural parts. We show existing approaches and new concepts and highlight difficulties and challenges.